2018
DOI: 10.1186/s40560-018-0281-0
|View full text |Cite
|
Sign up to set email alerts
|

The safety of a novel early mobilization protocol conducted by ICU physicians: a prospective observational study

Abstract: BackgroundThere are numerous barriers to early mobilization (EM) in a resource-limited intensive care unit (ICU) without a specialized team or an EM culture, regarding patient stability while critically ill or in the presence of medical devices. We hypothesized that ICU physicians can overcome these barriers. The aim of this study was to investigate the safety of EM according to the Maebashi EM protocol conducted by ICU physicians.MethodsThis was a single-center prospective observational study. All consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
3
19
0
6
Order By: Relevance
“…Forty one of 76 included studies provided the information on intubation type in patients undertaking EM-MV activities. Patients using tracheostomy undertaking EM-MV were reported in 33 studies [24, 3640, 42, 48, 51, 52, 57, 61, 6383]. The use of endotracheal tube (ETT) during EM-MV activities was reported in 32 studies [24, 35–40, 47, 48, 52, 54, 57, 61, 63, 6571, 77, 78, 8088].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty one of 76 included studies provided the information on intubation type in patients undertaking EM-MV activities. Patients using tracheostomy undertaking EM-MV were reported in 33 studies [24, 3640, 42, 48, 51, 52, 57, 61, 6383]. The use of endotracheal tube (ETT) during EM-MV activities was reported in 32 studies [24, 35–40, 47, 48, 52, 54, 57, 61, 63, 6571, 77, 78, 8088].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported that EM-MV was initiated using a protocol or an order. EM-MV was automatically triggered by a protocol to initiate activities following patients’ admissions to ICU in 31 studies [2426, 35–40, 42, 46, 49, 58, 60, 66, 67, 72, 7476, 80, 83, 84, 87, 93, 94, 101105]. Across the studies reporting the requirement of a formal order to initiate EM-MV, staff prescribing the order varied from physicians [43, 47, 64, 79, 86], PTs [48, 51, 68, 85], PTs and OTs [44, 71] to the care team [45].…”
Section: Resultsmentioning
confidence: 99%
“…A mobilization protocol for other patient populations might apply to patients with COVID-19 infections. In this setting, the aggressive involvement of intensivists, which was lower in this study, and a specialized mobilization program for patients with COVID-19 infections, considering the severity and phases of the lung injury, might facilitate the delivery of safe and e cient rehabilitation with appropriate considerations of risk [45]. Incorporating the dedicated use of ergometers and electrical muscle stimulation into the protocol may also promote rehabilitation.…”
Section: Discussionmentioning
confidence: 94%
“…Safety criteria also include termination criteria that indicate discontinuation of the early mobilization session and allow the patients to rest [ 61 ]. Studies performed by Liu et al [ 62 ] and Perme and Chandrashekar [ 63 ] have suggested criteria for termination of mobilization, which are stated in Table 8 .…”
Section: Resultsmentioning
confidence: 99%